ANALISIS KEMAMPUAN LITERASI MATEMATIKA SISWA KELAS 7 DALAM MENYELESAIKAN SOAL BILANGAN RASIONAL BENTUK PECAHAN DITINJAU DARI GENDER - Widyastuti, Arifah Dwi; Khotimah, Rita Pramujiyanti (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2025)
Mathematical literacy skills in Indonesia are still low, this can be seen in the 2022 PISA results which state that Indonesia scored below the average OECD standard score. This study aims to analyze junior high school students' mathematical literacy skills in solving fractional rational number problems in terms of gender. This type of research is descriptive qualitative. The subjects in this research were 32 class VII students of state junior high schools in Sukoharjo district who then selected 6 subjects to be interviewed. In this research, data collection was carried out using tests, documentation and interviews. This research used an instrument in the form of 3 questions on a mathematical literacy ability test on fractions and an interview guide. Data analysis in this research was carried out by data reduction, data presentation and conclusions. The results of this research show that in terms of indicators for formulating mathematical situations, male and female students have not been able to apply these indicators in all questions. This is based on student work results that do not match these indicators. In indicators using mathematical concepts, only LA, PA, and LB students were able to apply these indicators correctly. LA, PA, and LB students are able to answer questions by applying facts, rules, algorithms and mathematical structures correctly. Meanwhile, the third indicator was met by LA and LS students in question number 2 and LA, PA and LB students in question number 3.